Barabási-Type Laws of Success, Networks and Public Funds in Hungarian Science - Móczár, József (Public Finance Quarterly, 2023)
The book of Albert-László Barabási (2018) tested the laws of success in the American environment, therefore Barabási himself questioned how his laws function in an other environment, and whether his laws could actually be universal. The author formulated this question at the Central European University (CEU), at the excellently choreographed premiere of the book in September 2018, in Budapest. In this study, I analyse the Barabási-type laws of success, the role of networks and the reputation of public funds resulting from acclaim in Hungarian science.